Prevalence of Metabolic Syndrome in Young Patients with Acute ST Elevation Myocardial Infarction (STEMI) - Rameez Ahmed, Vashu Mal, Aijaz Ali, Farhan Memon, Lalchand, Tarique Ahmed, Ramsha Shahab, Shahzad, Saleem Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The metabolic syndrome is linked to several conventional and rising pro-thrombotic and pro-inflammatory cardiac risks. Most patients with cardiovascular disease have metabolic syndrome; however, the occurrence and connection of its various elements aren't obvious. There isn't any research regarding the occurrence of Metabolic Syndrome in young patients with acute STEMI. Objective: The purpose of this study was to figure out the occurrence of metabolic syndrome (MS) in young patients shown ST-Elevation Myocardial Infarction (STEMI) at a tertiary care hospital in Karachi, Pakistan. Material and Methods: The research was conducted on 170 patients with STEMI. Body mass index was measured. Smoking level, metabolic syndrome (MS), and aspects of the metabolic syndrome (BMI >23 kg meter per square, high blood pressure, hypertriglyceridemia, low-plasma HDLc, and affected fasting plasma glucose) were noted. Descriptive statistics were used, and stratification was done in the study. Fisher exact test and post-stratification by square test were used during the research study. P-value ≤0.05 was regarded as significant. Results: There were 42.2% women and 57.6% men with a mean age of 29.84±7.96 years. Metabolic syndrome (MS) was positive in 64.7 per cent of sufferers. BMI >23 kg meter per square was noticed in 97.1 per cent of patients. High blood pressure in 72.4 per cent of patients. Hypertriglyceridemia in 77.65 per cent of patients, Low plasma HDLc in 44.1 per cent of individuals, and affected fasting plasma glucose in 47.1 per cent of patients. Conclusion: It had been determined by research findings that the occurrence of metabolic syndrome in young patients having STEMI was higher. The common element was BMI >23 kg/m2, Hypertension, and Hypertriglyceridemia.